Fine Needle Aspiration Cytology vs. the Postoperative Histology – the Continuing Need for Multi-Disciplinary Approach? - Gill, G.; Kalyanasundaram, K.; Varughese, G.; Wilson, P.; Varadhan, L. (Experimental and Clinical Endocrinology & Diabetes, 2016)
We set out to investigate the concordance rates that were observed between fine needle aspiration cytology (FNA) compared with that of the post operative histology obtained for thyroid nodules over an 8 year period at a large university hospital.A retrospective analysis of 355 cases was conducted; patients operated for hyperthyroidism were excluded for the purposes of this study. We identified malignancy in a total of 101 cases (28%) The chance of malignancy with 2 Thy1 specimens was 5% in this study and 9% was observed in those with a Thy 2 FNA. On the converse, 7% of patient had malignant cytology on FNA though post-operative histology turned out to be benign.This therefore highlights the potential for discordance between thyroid FNA cytology and post-operative histology in the assessment of any thyroid nodule and thus reinforcing the need for a multidisciplinary approach in the assessment of all thyroid nodules.
Keywords: thyroid; graves-disease; cancer